GAMBARAN POLA KONSUMSI IBU MENYUSUI DAN KANDUNGAN Fe PADA AIR SUSU IBU DI KOTA BINJAI TAHUN 2016 - Debora Yossi Putri Pakpahan; Etti Sudaryati; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Breast Milk became the best food in the child's early life and the right base to grow and develop optimally. One of the problems in nursing mothers is not optimal milk production that so many infant that need undernutrition, which lead to health problems in infants including iron deficiency. Iron needs for infants is highly dependent on the iron content in breast milk obtained from the consumption of foods and patterns by nursing mothers to be considered.This study aims to describe the pattern of consumption nursing mothers and the Fe content in breast milk in three sub-districts in the city that is North Binjai, East Binjai and West. This study was an observational cross-sectional design with clutser sampling. This study population is 1884 mothers breastfeeding babies with a sample of 60 people. The data collection by using the form method of 24 hours food recall and food frequency.The results of this reseach showed that the types of foods high in iron that often consumed by the respondents, tempeh, tofu, eggs and fish wet and type of foood low in iron that often consumed by the respondent is bread. The test results Fe content in breastmilk obtained with an average of 10.39 mg / ml and there are 60 respondents, it is as many as 34 people (56.7%) of respondents have classified the Fe content is below the average. There are 57 people (95%) of respondents with the level of consumption of iron is less. There are 33 people (57.9%) of respondents who has a consumption the level of consumption of iron lack the Fe content of breast milk classifield as below average. Mother suggested further increase the consumption of food sources of energy, protein and especially sources of iron with iron by utilizing resources of iron are available and diverse. Keywords: breast milk, food consumption, Fe content